Resistivtiy Structure in Kamojang Geothermal Field Derived from CSAMT Data - Enjang Jaenal Mustopa; Wahyu Srigutomo; Doddy Sutarno; Umar Fauzi (Indonesian Journal of Physics, 2011)
Controlled-source audio frequency magnetotelluric (CSAMT) survey consisting of 60 soundings has been carried out in the Kamojang geothermal field to delineate resistivity structure correlated to the present geothermal reservoir. The transmitter site was located about 3 − 5 km in the south-west of the survey area. The sounding sites were distributed irregularly and the distance between each of them varied from 200 to 500 m, covering the Kamojang Geothermal area. The two dimensional (2D) inversion scheme was applied to interpret the CSAMT data. The results show that the subsurface resistivity structures in the Kamojang geothermal field consists of three types of resistivity features correlated to the existing geothermal reservoir in the area, that is, the overburden (first layer) having resistivity value of 30 – 150 ohm.m and thickness of 30 to 100 m overlaying the intermediate (second) layer which has an extremely low resistivity of 3 – 10 ohm.m with 500 – 1200 m thick. This low resistivity layer can be considered as a hydrothermal alteration zone comprising the impermeable layer or sealing cap rock. Finally, the third layer which is relatively more resistive than the second layer with resistivity of 30 − 100 ohm-m. From the 3D view of the low resistivity anomaly (<10 ohm.m) considered as a hydrothermal alteration zone, it is obtained that altered zone is deep in the south-west and becomes shallow in the north-east of the area.